Improving the care for people with acute low-back pain by allied health professionals (the ALIGN trial): A cluster randomised trial protocol - McKenzie, Joanne E; O'Connor, Denise A; Page, Matthew J; Mortimer, Duncan S; French, Simon D; Walker, Bruce F; Keating, Jennifer L; Grimshaw, Jeremy M; Michie, Susan; Francis, Jill J; Green, Sally E (Université d'Ottawa | University of Ottawa, 2010)
Abstract Background Variability between clinical practice guideline recommendations and actual clinical practice exists in many areas of health care. A 2004 systematic review examining the effectiveness of guideline implementation interventions concluded there was a lack of evidence to support decisions about effective interventions to promote the uptake of guidelines. Further, the review recommended the use of theory in the development of implementation interventions. A clinical practice guideline for the management of acute low-back pain has been developed in Australia (2003). Acute low-back pain is a common condition, has a high burden, and there is some indication of an evidence-practice gap in the allied health setting. This provides an opportunity to develop and test a theory-based implementation intervention which, if effective, may provide benefits for patients with this condition. Aims This study aims to estimate the effectiveness of a theory-based intervention to increase allied health practitioners' (physiotherapists and chiropractors in Victoria, Australia) compliance with a clinical practice guideline for acute non-specific low back pain (LBP), compared with providing practitioners with a printed copy of the guideline. Specifically, our primary objectives are to establish if the intervention is effective in reducing the percentage of acute non-specific LBP patients who are either referred for or receive an x-ray, and improving mean level of disability for patients three months post-onset of acute LBP. Methods The design of the study is a cluster randomised trial. Restricted randomisation was used to randomise 210 practices (clusters) to an intervention or control group. Practitioners in the control group received a printed copy of the guideline. Practitioners in the intervention group received a theory-based intervention developed to address prospectively identified barriers to practitioner compliance with the guideline. The intervention primarily consisted of an educational symposium. Patients aged 18 years or older who visit a participating practitioner for acute non-specific LBP of less than three months duration over a two-week data collection period, three months post the intervention symposia, are eligible for inclusion. Sample size calculations are based on recruiting between 15 to 40 patients per practice. Outcome assessors will be blinded to group allocation. Trial registration Australian New Zealand Clinical Trials Registry ACTRN12609001022257 (date registered 25th November 2009)